Stunting Reduction in Sub-Saharan Africa - World Bank Group (World Bank, Washington, DC, 2018)
Reducing all forms of malnutrition, including stunting, is central to the World Bank Group's twin goals of ending extreme poverty and promoting shared prosperity, as well as building resilience and preventing instability. Maternal and child under nutrition is estimated to be responsible for about 45 percent of child mortality and 11 percent of the global disease burden. Conversely, reductions in stunting are estimated to potentially increase overall economic productivity, as measured by GDP per capita, by 4 to 11 percent in Africa and Asia – making investments in early nutrition one of the most cost-effective development actions to yield permanent and inalienable benefits.Since 2000, progress in stunting reduction has been slower in Africa than in other regions. While both Asia and Latin America and Caribbean have managed to reduce stunting rates by over one third, Africa saw a reduction of only one sixth during the same period. In 2016, over 40 percent of the 159 million stunted children globally were in Africa (UNICEF, WHO, and World Bank, 2016). Accelerating the reduction of stunting in Africa will be key to maximizing the return on investments in early childhood development, in education, and more broadly in policies aimed at fostering and enhancing human capital accumulation and job creation.This report consists of seven chapters. The first chapter focuses on the income elasticity of stunting reduction in Sub-Saharan Africa. Chapters second through seventh focus on the potential financing needs and impacts of investing in scaling up stunting reduction interventions in the Africa region as a whole, and in five of the high-burden countries in Africa (Benin, Côte d’Ivoire, Ethiopia, Niger, and Rwanda). While the first chapter offers a broad assessment of the empirical relationship between income and stunting reduction at the aggregate level across countries, the subsequent chapters focus on country specific policy recommendations designed to accelerate progress in stunting reduction.